LEGAL REGULATIONS TO EQUALIZE THE CONDITIONS OF EMPLOYMENT INTO STATE OFFICIAL SERVICE IN OTTOMAN EMPIRE - MEHMET AYKANAT (Journal of Ottoman Legacy Studies, 2019)
In the classical period, the Ottoman Empire created a unique state official system. In this system, non-Muslim citizens were not given equality in state official systems. However, in the Tanzimat period the Empire tried to achieve this equality for various reasons. Equality provisions are included in the constitution, constitutional documents and various laws. The legal regulations of the Ottoman Empire aiming to provide equality in access to the state official employment are not examined. The contents of these legal regulations have not been adequately evaluated in terms of access to the state official employment. The principles and conditions of employment have not been compared with today's regulations. The studies are mostly concentrated in the field of application and the theoretical part of the subject is omitted. This study sets out the basic legal arrangements aimed at equalizing the employment requirements for the state officials. These regulations appear to be sufficient in terms of the principles and conditions of employment of state officials. It is understood that the Ottoman Empire established the system of employment into the modern state official position with these regulations.